Yeast artificial chromosomes: an alternative approach to the molecular analysis of mouse developmental mutations. - Larin, Z; Lehrach, H (1990)
Mammalian genetics now allows a molecular study of genomic regions previously analysed by genetic and embryological techniques. To simplify such an analysis, we have established a number of libraries of mouse DNA in Yeast Artificial Chromosome (YAC) vectors, constructed either by partial digestion with EcoRI, or by complete digestion with enzymes which cut rarely in the mammalian genome. In this paper we report the construction of complete digest libraries prepared from mouse genomic DNA using the rare cutter enzymes NotI and BssHII, and the detection of gene loci from the H-2 complex, the t-complex, and other loci from the mouse genome. Due to their large insert size, YAC clones simplify the cloning of extended regions of the mouse genome surrounding known developmental mutations and should, after introduction into the germ line, offer a high probability of correct expression of the genes contained within the cloned region. We hope that this will allow the use of YAC clones to scan regions of interest such as the t-complex for specific genes by testing DNA introduced into transgenic mice for the ability to complement mutations localised to this region.